2015
DOI: 10.1074/jbc.m115.637207
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recognition Preferences of the Three Src Homology 3 (SH3) Domains from the Adaptor CD2-associated Protein (CD2AP) and Direct Association with Ras and Rab Interactor 3 (RIN3)

Abstract: Background:The CD2AP adaptor facilitates cell signaling using its in-built interaction modules (SH3 domains). Results: RIN3 was characterized as a novel CD2AP SH3 binding protein by biophysical and biochemical methods. Conclusion: CD2AP has many potential interactors and is probably a cellular hub. Significance: We reveal how protein modules can interact with families of related recognition motifs rather than a single motif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 71 publications
(48 reference statements)
5
40
0
Order By: Relevance
“…For example, if a Lys (e.g., K114 in CD2AP) is replaced by a charge-neutral amino acid (e.g., Q 104) in CIN85, the structure difference may be minimal, but the difference in affinity for the interface at the binding partner might be rather large. This is underlined by a recent study employing flanking residue permutation arrays in the CD2AP-binding protein, ALIX, where selectivity could be achieved even between the three SH3 domains (28). Similar effects were also reported for the CIN85 SH3 domains (29).…”
Section: Discussionsupporting
confidence: 59%
“…For example, if a Lys (e.g., K114 in CD2AP) is replaced by a charge-neutral amino acid (e.g., Q 104) in CIN85, the structure difference may be minimal, but the difference in affinity for the interface at the binding partner might be rather large. This is underlined by a recent study employing flanking residue permutation arrays in the CD2AP-binding protein, ALIX, where selectivity could be achieved even between the three SH3 domains (28). Similar effects were also reported for the CIN85 SH3 domains (29).…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, the SLC24A4 locus harbors a small LD block with 46 SNPs that all reside within an intron of SLC24A4 . Previous work has implicated both SLC24A4 and the nearby Ras And Rab Interactor 3 ( RIN3 ) gene in this association but the true mediator remains unclear 44, 45 . Our multi-omic approach identifies a single SNP, rs10130373, which occurs within a microglia-specific peak, disrupts an SPI1 motif, and communicates specifically with the promoter of the RIN3 gene (Figure 4f-g).…”
Section: Resultsmentioning
confidence: 99%
“…Structural Insights into Class III and IV Specificities Class III and class IV contain three domains each that prefer À6 RxxxxxP 0 (+) or 0 PxxxxR +5 (À) motifs, respectively, in which there is no specificity at the position that would be occupied by the proximal Pro residue in canonical class I or II domains, respectively ( Figures 3A and 3B). Notably, the six key positions forming the PXXP-binding site in these domains are conserved at the sequence level (Table S1), and the structures of CD2AP-1/3 and CD2AP-2/3 (Rouka et al, 2015) show that they can bind to class II peptides ( Figures 4D and 3E, respectively). However, in agreement with our results, peptide arrays and affinity assays (Rouka et al, 2015) have shown that 0 Px[P/ A] +2 xxR +5 (À) is the preferred binding motif for these domains and Pro +3 is not required for ligand recognition ( Figure 3B).…”
Section: Structural Insights Into Class I and Ii Specificitiesmentioning
confidence: 99%
“…Notably, the six key positions forming the PXXP-binding site in these domains are conserved at the sequence level (Table S1), and the structures of CD2AP-1/3 and CD2AP-2/3 (Rouka et al, 2015) show that they can bind to class II peptides ( Figures 4D and 3E, respectively). However, in agreement with our results, peptide arrays and affinity assays (Rouka et al, 2015) have shown that 0 Px[P/ A] +2 xxR +5 (À) is the preferred binding motif for these domains and Pro +3 is not required for ligand recognition ( Figure 3B). Given that the PXXP-binding site is conserved, it is not clear why these domains do not exhibit preference for a proximal Pro, but it is possible that substitutions within the hydrophobic core might alter peptide-binding specificity, as has been reported for some DNA-binding domains (Koulechova et al, 2015).…”
Section: Structural Insights Into Class I and Ii Specificitiesmentioning
confidence: 99%